2020
DOI: 10.1097/bpo.0000000000001202
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Early-onset Scoliosis: Growing Rods Versus Vertically Expandable Prosthetic Titanium Ribs at 5-year Follow-up

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The incidence of IF in the present cohort was lower than those of previous studies; this may be attributed to the same cause as the low incidence in TGRs. In contrast, the results of this study were consistent with those of a previous study comparing TGRs and VEPTRs, which found no significant difference in IF incidence between the two surgical methods [ 18 ]. Magnetically controlled growth rods, which eliminate the need for multiple lengthening surgeries and the accompanying general anesthesia and skin incisions, have recently been implemented in Europe and the United States; however, the complication rates were reported not to be lower than those of TGRs [ 7 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of IF in the present cohort was lower than those of previous studies; this may be attributed to the same cause as the low incidence in TGRs. In contrast, the results of this study were consistent with those of a previous study comparing TGRs and VEPTRs, which found no significant difference in IF incidence between the two surgical methods [ 18 ]. Magnetically controlled growth rods, which eliminate the need for multiple lengthening surgeries and the accompanying general anesthesia and skin incisions, have recently been implemented in Europe and the United States; however, the complication rates were reported not to be lower than those of TGRs [ 7 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…At a mean follow-up of eight years, growing rod patients had a significantly greater correction in Cobb angle (50% versus 27%; p = 0.001) as well as greater gain in thoracic height compared to VEPTR patients (24% versus 12%; p = 0.024). VEPTR patients also had a greater progression in their kyphosis postoperatively [9].…”
Section: Discussionmentioning
confidence: 89%
“…McElroy et al found that 19 (70%) of 27 patients experienced a complication following growing rod surgery, which predominantly included deep wound infections necessitating early fusion and instrument removal in a few patients, as well as rod exchange and rod fracture [6]. However, Bachabi et al found a higher complication rate in VEPTRs when directly compared to growing rod surgery (82% versus 66%) and specifically in wound complications (41% versus 14%; p = 0.011) [9].…”
Section: Discussionmentioning
confidence: 99%
“…As in the main texts, the data were not separated out, so we included them in the TGR group, as the vast majority were treated with this system. Papers by Akbarnia et al [ 10 ], Bachabi et al [ 11 ], Haapala et al [ 12 ], Andras et al [ 13 ], and Luhmann et al [ 14 ], dealt with comparisons between TGR and MCGR, TGR, and VEPTR, Shilla and MCGR, and TGR and Shilla, respectively, so they appear in the table for the applicable system. The demographic findings of the included articles are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%